Azure Cosmos DB Developer Specialty (DP-420) certification course - Batra, Mohit (O'Reilly Media, Inc., 2025)
Today's applications need to work with large volumes of data-be it in eCommerce, social media, fraud detection, or personalization. For this ever-growing amount of data, organizations need robust, highly scalable, extremely fast, and low-cost data stores. Microsoft Azure Cosmos DB provides just that. A NoSQL, cloud-based platform, Azure Cosmos DB is suitable for handling mission critical workloads, storing vast amounts of semi-structured data that can cater to a variety of use cases, and building truly global applications. In this on-demand course, you will learn about the fundamentals of Azure Cosmos DB for managing data and building applications. Through concise video presentations and interactive quiz assessments, the course will review how to get started with Cosmos DB, how to build a data model, how to manage data, build applications and run queries on it, how to integrate the database with other Azure services to create solutions, and how to optimize, secure, deploy, and monitor these solutions.
Online resource; title from title details screen (O'Reilly, viewed January 21, 2025)
Keywords: Cloud computing -- Study guides -- Examinations; Microsoft Azure (Computing platform) -- Study guides -- Examinations; Microsoft Azure (Plateforme informatique); Examens; Guides de l'étudiant; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet